Historical Review of Ulama and Umara’ Relations and Its Implications for Islamic Da’wah - Mastori Mastori; Zenal Arifin; Sunardi Bashri Iman (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study seeks to analyze the relationship between ulama and umara' and their implications for Islamic da'wah. The research was conducted by exploring historical and empirical sources related to the relationship between the ulama and umara' past and present which is reflected in the various political thoughts and policies of the ulama and umara'. The data was collected through observation and literature study while the data were analyzed using a descriptive qualitative approach. The results of the study show that historically the relationship between ulama and umara' occurred dynamically. During the past Islamic empires, the relationship between ulama and umara' was collaborative and even integrative. While in later times the relationship between ulama and umara' tended to be secularistic-pragmatic. The implication of this integrative relationship is that Islamic da'wah can develop rapidly so that Islam becomes the religion of the majority of the Indonesian people. Meanwhile, pragmatic secularistic relations made da'wah stagnant due to the weak involvement of umara' in the process of IslamizationPenelitian ini berupaya untuk menganalisis relasi ulama dan umara’ dan implikasiinya bagi dakwah Islam. Penelitian dilakukan dengan menggali sumber-sumber historis dan empiris terkait hubungan ulama dan umara’ masa lalu dan saat ini yang tercermin dalam beragam pemikiran dan kebijakan politik ulama dan umara’. Pengumpulan data dilakukan melalui observasi dan studi pustaka sedangkan data dianalisis dengan pendekatan kualitatif deskripstif. Hasil penelitian menunjukan bahwa secara historis relasi ulama dan umara’ terjadi secara dinamis. Pada masa kerajaan Islam masa lalu hubungan ulama dan umara’ terjadi secara kolaboratif bahkan integratif. Sementara pada masa sesudahnya hubungan ulama dan umara’ cenderung sekuleristik-pragmatik. Implikasi dari hubungan integratif adalah dakwah Islam dapat berkembang secara cepat sehingga Islam menjadi agama mayoritas rakyat Indonesia. Sementara hubungan sekuleristik pragmatik membuat dakwah stagnan karena lemahnya keterlibatan umara’ dalam proses islamisasi.